Drugs used in prostatic enlargement and lower urinary tract symptoms: unseen and overlooked effects on sexual health (BIRDEM Medical Journal, 2019)
Benign prostatic hyperplasia (BPH) is one of the most common genitourinary complications in men over 50 years of age and typically presents with lower urinary tract symptoms (LUTS) and may need medical and occasionally surgical interventions. Few of them may only need advice on behavioral modification like less water intake after sunset, avoid tea, coffee after evening, avoid alcohol and less use of diuretics. The symptoms related to BPH or LUTS without any prostatic enlargement are incomplete voiding, frequency, intermittency, urgency, weak stream, straining and nocturia. For most patients with mild to moderate symptoms of BPH [International Prostate Symptom Score (IPSS)